The global burden of lead exposure-related ischemic stroke: based on Bayesian age-period-cohort analysis - Chen, Xiaofang; Zhao, Lihua; Wu, Xiaxia; Chen, Dan; Yao, Mingya (Frontiers in Public Health, 2025)
IntroductionThe global burden of lead exposure-related ischemic stroke poses a significant concern for public health, and this study aimed to comprehensively analyze the current situation, the change patterns, and forecast potential future trends associated with this critical issue.MethodsThe Global Burden of Disease (GBD) 2019 dataset was analyzed to assess the burden of lead exposure-related ischemic stroke. Comparison of the 2019 disease burden was conducted across age, gender, Sociodemographic Index (SDI) regions, and GBD regions. Linear regression models were used to calculate the estimated annual percentage change (EAPC) values, exploring trends from 1990 to 2019. Cluster analysis identified patterns of changing disease burden across GBD regions. Bayesian age-period-cohort (BAPC) analysis was performed to predict future burden trends.ResultsIn 2019, lead exposure-related ischemic stroke caused a significant disease burden, with males and middle-aged/older adults disproportionately affected. The highest burden was observed in middle/low-middle SDI regions. From 1990 to 2019, the age-standardized deaths rate (ASDR) of deaths and disability-adjusted life-years (DALYs) exhibited a rise-and-fall pattern, with absolute cases increasing. Males consistently carried a heavier burden, and age groups exhibited variable patterns but generally followed the overall trend. High SDI regions saw a decline in burden, whereas other regions mirrored the global pattern. Clustering analysis revealed region-specific variations. The BAPC model predicts differing global trends in lead exposure-related ischemic stroke burden genders, with females expecting stable cases but decreasing rates, while males anticipate declines in all indicators over the next 11 years.ConclusionThe global burden of lead exposure-related ischemic stroke is a pressing issue that requires urgent attention. Our findings underscore the need for enhanced surveillance, prevention, and treatment strategies to mitigate this burden.